Communication Dynamics and Elite Perceptions: Assessing Government Policy Effectiveness in Sumberglagah Leprosy Village, Indonesia - Hidayat, Endik; Susilo, Daniel; Ansyah, Rahmat Hussein Andri; Dizon, Carl C.G. (Nyimak: Journal of Communication, 2024)
Stigma and discrimination continue to persist in the leprosy village of Sumberglagah, despite government efforts to provide social assistance and community empowerment programs. This article aims to uncover the dynamics of communication and the perceptions of village elites and community members regarding the effectiveness of various government policies targeting Sumberglagah. Utilizing elite theory and a three-dimensional framework—cognitive, affective, and conative—the study employs a mixed-methods approach. Qualitative data were gathered through interviews with five elite village informants, while quantitative data were collected from a survey of 100 respondents in Tanjungkenongo village. Findings indicate that, from the elite perspective, government programs are perceived as relatively ineffective in addressing the needs of the leprosy community, primarily due to a culture of reliance on external assistance from both government and non-government sources. In contrast, quantitative analysis reveals that the community generally expresses satisfaction with government programs, with an average satisfaction score exceeding 4. However, there is notable skepticism regarding the long-term impact of these programs, as reflected in the low community engagement with government-initiated empowerment programs. This study highlights the divergence in perceptions between elites and the community concerning government interventions, emphasizing the need for more effective and culturally attuned strategies to address the unique challenges faced by leprosy-affected communities.Keywords: Policy; Elite; Village Community; LeprosyAbstrakStigma dan diskriminasi masih terjadi di desa leprosy Sumberglagah, meskipun pemerintah telah berupaya memberikan program bantuan sosial dan pemberdayaan masyarakat. Artikel ini bertujuan untuk mengungkap dinamika komunikasi dan persepsi elit desa serta masyarakat terkait efektivitas berbagai kebijakan pemerintah di Sumberglagah. Dengan menggunakan teori elit dan kerangka tiga dimensi—kognitif, afektif, dan konatif—penelitian ini mengadopsi pendekatan metode campuran. Data kualitatif diperoleh dari wawancara dengan lima informan elit desa, sementara data kuantitatif diperoleh melalui survei terhadap 100 responden di desa Tanjungkenongo. Temuan menunjukkan bahwa dari perspektif elit, program pemerintah cenderung dianggap kurang efektif dalam memenuhi kebutuhan komunitas leprosy, disebabkan oleh budaya ketergantungan pada bantuan dari pihak pemerintah dan non-pemerintah. Sebaliknya, analisis kuantitatif mengungkapkan bahwa masyarakat umumnya merasa puas dengan program pemerintah, dengan rata-rata skor kepuasan melebihi 4. Namun, terdapat skeptisisme mengenai dampak jangka panjang dari program tersebut, tercermin dari rendahnya partisipasi masyarakat dalam program pemberdayaan yang diinisiasi pemerintah. Penelitian ini menyoroti perbedaan persepsi antara elit dan masyarakat tentang intervensi pemerintah, menekankan perlunya strategi yang lebih efektif dan sesuai dengan konteks budaya untuk menghadapi tantangan unik yang dihadapi komunitas yang terkena dampak lepra.Kata Kunci: Kebijakan; Elit; Masyarakat Desa; Kusta